La génesis de Nosferatu en el cine mudo - Barr, Amanda M. (Kansas State University, 2008)
This thesis analyses the play Nosferatu by the contemporary Spanish author Francisco Nieva, and more specifically focuses on its genesis in silent film, primarily German Expressionist. First we take a look at the genre and style of the work itself, followed by a history of the vampire in literature and film. After a brief summary of the play, we begin to focus on the films, first discussing how Nieva came into contact with them in France through the cinémathèques. What follows is a detailed study of the films, with summaries, analysis of themes, and finally a comparison to Nosferatu, looking at the elements of the play that each film directly influenced.
Keywords: Nosferatu; Francisco Nieva; Expressionist cinema; Spanish theatre; Theater (0465)